"It's about a Life Worth Living": Rosalie A. Kane, PhD, Pioneer of Quality of Life Measurement in Long-Term Care. Issue 1 (2nd January 2021) - Gaugler, Joseph E.; Shippee, Tetyana P.
ABSTRACT: This contribution to the special issue celebrating Dr. Kane's legacy in the Journal of Gerontological Social Work highlights her significant scholarly achievements in the measurement of quality of life in long-term care. Following a synthesis of Dr. Kane's groundbreaking work in this area, we summarize how her study of the measurement of quality of life has served as the foundation for significant practice/policy advancements. We conclude that Dr. Kane and her ongoing legacy in the rigorous measurement of quality of life has achieved her ultimate aspiration: the elevation of quality of life as the central concern when selecting, using, delivering, and valuing long-term care.